구명조끼 의무착용을 통한 연안 활동자의 안전 증진 방안 연구 - 하민재; 이영찬 (한국해양경찰학회보, 11(2), 2021)
이 연구는 연안 활동자의 안전을 증진할 수 있는 방안 마련을 목적으로, 최근 이용객 증가에 따라 급증하고 있는 연안 사고 발생 현황 분석을 통하여 연안에서 특정 행위 시 구명조끼 착용의 필요성을 고찰하였고, 해상 조난 사고와의 비교를 통하여 연안 사고의 심각성 도출과 안전 장비 착용의 필요성을 제시하였다. 해상에서의 낚시 행위는 수상레저안전법에 따라 구명조끼 등 안전 장비를 반드시 착용해야 하나 계속적인 사고가 발생하는 연안지역 낚시 행위자에 대하여는 개인 안전 관련 법규정이 부재하여 법의 사각지대에 놓여 있는 상황이다. 이에 대해 국내·외 연구 결과와 해외사례의 조사를 통하여 구명조끼의 효과성에 대하여 고찰하였고, 사고통계와 연안 이용방법 등을 고려하여 구명조끼 의무착용 대상 장소 영역과 대상 행위를 도출 하였으며, 이러한 연구 내용들을 바탕으로 법제안을 제시하였다. 추후 연안에서의 낚시 행위자의 구명조끼 의무 착용을 위한 다각적이고 지속적인 검토와 연구가 필요하 며, 이러한 과정을 통해 법제화 및 법안 시행에 대한 환경조성이 필요한 것으로 판단된다. This study investigated the necessity of wearing a life jacket during certain activities on the coast through analysis of the current status of coastal accidents that have been increasing rapidly with the recent increase in users, with the aim of preparing measures to improve the safety of coastal activists. Through the comparison with, the seriousness of coastal accidents and the necessity of wearing safety equipment were suggested. For fishing at sea, safety equipment such as a life jacket must be worn in accordance with the Water Leisure Safety Act, but there are no personal safety related laws and regulations for fishing actors in coastal areas where continuous accidents occur, so they are in the blind spot of the law. In this regard, the effectiveness of life jackets was reviewed through domestic and international research results and overseas case studies, and based on these research contents, the area of the place where life jackets are obligated to be worn and the target behaviors were derived, and a legal proposal was presented. Through this study, a legislation was proposed to improve coastal safety due to obligatory wearing of life jackets by fisher in coastal areas. It is judged that the composition is necessary. KCI Citation Count: 0